Sulūk al-Qāḍī: Muqāranah Bayna Mafhūm al-Māwardī fī Kitāb Adab al-Qāḍī wa Qawā’id Sulūk al-Qaḍa fī Indūnīsiyā - Yayan Sopyan; Syamsudin Syamsudin (AHKAM : Jurnal Ilmu Syariah, 2021)
This study compares the Judicial Code of Conduct formulated by the Supreme Court of Indonesia and the classical Islamic jurisprudence using the case of the book of Adab al-Qāḍī by Al-Māwardī. The study uses a comparative legal approach to see how these two concepts discuss the integrity of judges. This study found that the Judicial Code of Conduct in Indonesia comes from Islamic law, which Al-Māwardī also uses. The Judicial Code of Conduct concept in Indonesia is in line with the theory of moral idealism, which views humans as moral beings who serve as guidelines for human attitudes and behavior. This is in line with the idea of the unity of the relationship between law and morality. Not all Code of Judicial Ethics in the book "Adab al-Qāḍī " is relevant in Indonesia. However, it cannot be ignored the importance of this book as one of the references in preparing the Judicial Code of Conduct in Indonesia.  Abstrak: Penelitian ini membandingkan Kode Etik Peradilan yang dirumuskan oleh Mahkamah Agung Indonesia dan yurisprudensi Islam klasik yang berdasar kitab Adabu al-Qāḍī karya Al-Māwardī. Kajian ini menggunakan pendekatan hukum komparatif untuk melihat bagaimana kedua konsep tersebut membahas integritas hakim. Kajian ini menemukan bahwa Kode Etik Peradilan di Indonesia bersumber dari hukum Islam, yang juga digunakan oleh Al-Māwardī. Konsep Kode Etik Peradilan di Indonesia sejalan dengan teori idealisme moral yang memandang manusia sebagai makhluk bermoral yang menjadi pedoman sikap dan perilaku manusia. Hal ini sejalan dengan gagasan kesatuan hubungan antara hukum dan moralitas. Adapun Kode Etik Peradilan yang terdapat dalam Adab al-Qāḍī tidak semuanya relevan untuk diterapkan di Indonesia. Namun demikian, buku ini tetap penting untuk dijadikan salah satu acuan dalam penyusunan Kode Etik Peradilan di Indonesia.